The Influence of Market Sentiment on Tesla’s Valuation : A Combined Fundamental and Sentiment-Driven Approach - Wohl, Adam; Krabec, Tomáš, 1981-; Poborský, František; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This thesis examines whether investor sentiment propels Tesla Inc.’s daily stock returns between 1 Jan 2021 and 30 Apr 2025. Roughly 0.6 million Tesla-focused items - tweets, Reddit comments, and news headlines—are scored with FinBERT and validated with VADER, then matched to returns and standard market controls. Ordinary Least Squares shows significant positive sentiment–return links across all three platforms, with Twitter displaying the strongest statistical significance; VADER adds no explanatory power once FinBERT is used. Trailing PE multiples do not materially alter these relationships. Vector-autoregressive Granger-causality tests confirm directionality: Twitter sentiment predicts next-day returns, whereas price moves largely drive subsequent tone on Reddit and in traditional news. The study underscores Twitter’s predictive edge for a high-profile, retail-driven stock and demonstrates that sentiment effects operate independently of fundamental valuation multiples.
Vedoucí práce: Tomáš Krabec
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses